2022
DOI: 10.3390/polym14102114
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Release Formulation of Inhaled Beclomethasone Dipropionate-Hydroxypropyl-Beta-Cyclodextrin Composite Particles Produced Using Supercritical Assisted Atomization

Abstract: In this study, the enhanced solubilization performance of a poorly soluble drug, beclomethasone dipropionate (BDP), was investigated using hydroxypropyl-β-cyclodextrin (HP-β-CD) and ethanol. The enhanced solubility of the drug was determined using the phase solubility method and correlated as a function of both HP-β-CD and ethanol concentrations. The effective progress of drug solubility originated from the formation of cyclodextrin and BDP inclusion complexes and increase in the lipophilicity of the medium, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The loaded microparticles showed a larger mean diameter with respect to the sodium alginate microparticles obtained at the same alginate concentration; in particular, the diameter changed from 0.46 ± 0.18 µm for sodium alginate microparticles to 0.72 ± 0.25 µm for sodium alginate plus salicylic acid microparticles. This result can be a consequence of the solution viscosity increase due to the presence of the drug [ 18 , 25 , 27 ], and this effect is also visible comparing the PSDs of these two different samples, as shown in Figure 5 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The loaded microparticles showed a larger mean diameter with respect to the sodium alginate microparticles obtained at the same alginate concentration; in particular, the diameter changed from 0.46 ± 0.18 µm for sodium alginate microparticles to 0.72 ± 0.25 µm for sodium alginate plus salicylic acid microparticles. This result can be a consequence of the solution viscosity increase due to the presence of the drug [ 18 , 25 , 27 ], and this effect is also visible comparing the PSDs of these two different samples, as shown in Figure 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a good reproducibility in terms of particle size and size distribution can be assured, avoiding aggregation phenomena among particles [ 23 ]. Using this technique, several compounds have been co-precipitated [ 24 , 25 ], with the aim of improving the dissolution rate and thus the bioavailability of poorly water-soluble active pharmaceutical ingredients [ 26 ], controlling the drug release time and mechanism from the microcarrier [ 27 ], and producing microdevices for biomedical applications [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…An aqueous solution containing 5% ( w / v ) HP-β-CD increased the solubility of BDP to 37.2 mg/L, which is 133 times that of the intrinsic BDP solubility. Therefore, the dissolution test results of the BDP–HP-β-CD composites and the as-received BDP demonstrated that the reciprocal of the estimated time of 63.2% drug release from BDP–HP-β-CD composites was approximately five times that of the as-received BDP [ 11 ]. In this study, a 5% ( w / v ) γ-CD solution increased the solubility of BDP in aqueous solution to 93.5 mg/L, thus indicating that the efficiency of γ-CD in improving BDP solubility was better than that of HP-β-CD and accompanied by fast dissolution of BDP–γ-CD formulation.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the study by Suzuki et al [ 10 ] develop roflumilast dry powder by dissolving HP- β -CD in ethanol prior to spray drying. Significantly, our previous study focused on the preparation of BDP−HP- β -CD composites using a supercritical assisted atomization (SAA) technique for the purpose of immediate drug release [ 11 ]. In the formulation, HP- β -CD functions as a carrier or solubilizer, and LEU enhances the homogeneity of the API.…”
Section: Introductionmentioning
confidence: 99%
“…Cooling crystallization has gained considerable attention due to its low energy consumption and the high purity of the resulting ICs. Recent advances in the field have led to the development of novel techniques such as supercritical anti-solvent and supercritical assisted atomization, which have also been explored for the preparation of ICs [23,24]. 9-Fluorenone (Figure 1A), also known as diphenylene ketone, is a common smallmolecule OPAH and a frequently used fine chemical raw material [7].…”
Section: Introductionmentioning
confidence: 99%